1879 Gen. and Local Laws of the State of Ohio 191-92, An Act to define and suppress tramps, § 2 (vol. 76) - (:unkn) unknown (General Publisher, 1879)
That any tramp who shall enter any dwelling-house, or shall enter the yard or enclosure about any dwelling-house, against the will or without the permission of the owner or occupant thereof, or shall not, when requested, immediately leave such place, or shall be found carrying any fire-arms or other dangerous weapons, or shall do or threaten to do any injury to any person, or shall do or threaten to do any injury to the real or personal estate or property of another, shall, upon conviction thereof, be imprisoned in the penitentiary not less than one year nor more than three years.
--
Keywords: CARRY - DANGEROUS PERSONS